Analisis Kelayakan Video Pembelajaran Berbasisi Platform Youtube Melalui Pembelajaran Ips Di Sd - Safa, Libie Siti (Didaktika, 2022)
The purpose of this study is to analyze educational video content on the YouTube platform. This study aims to examine and describe educational video content on the Natural Resources YouTube platform. The YouTube platform is often used as a source for uploading educational content in the form of learning videos and also learning videos that are still on the YouTube platform are often used as a teacher's learning media, but the learning content on videos has not been demonstrated. be possible. To assess the reliability of learning films, it is necessary to analyze learning videos on the YouTube platform, using a qualitative approach using content analysis research methods. In particular, data collection is carried out through the YouTube platform using the key term "Class IV Social Science Learning Natural Resources Materials", the video is then analyzed from the established standards (BSNP). Using aspects of the feasibility of material content, presentation, language graphics. The results of the study analyzed 12 social studies learning videos on YouTube according to the channel, using a homogeneous presentation of content aspects as much as 87.7% with a very decent category, homogeneous -homogeneous presentation percentage as much as 85% included in the very feasible category, the percentage of language in homogeneous learning videos as much as 78, 7% with a decent category, homogeneous presentation on learning video learning videos as much as 98.6% is included in the very feasible category. These four criteria indicate that social studies learning videos are valuable as teaching tools.